2020
DOI: 10.1136/vr.105671
|View full text |Cite
|
Sign up to set email alerts
|

Significant variation in the management of cull sows before transport for slaughter: results from a survey of Danish pig farmers

Abstract: BackgroundApproximately 50% of sows are slaughtered each year, but management of cull sows is not well described.MethodsWe aimed to describe how cull sows are sent to slaughter using a questionnaire survey emailed to 885 Danish pig farmers, including questions about the use of pick-up facilities (either a designated pen used for reasons of biosecurity and practicality, in a special part of the barn, where pigs are kept in the last hours before being loaded onto a commercial truck, or a stationary vehicle kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
(41 reference statements)
1
26
1
Order By: Relevance
“…He argues that effectiveness of driver-initiated initiatives, to avoid additional suffering likely to be associated with transport of a compromised animal are questionable, and that there are different views about the types of conditions that constitute a compromised animal. In our recent survey among farmers delivering sows to the same slaughterhouse as in the present study ( Herskin et al, 2020 ), the reported use of the special condition transport was even lower than in the present one. Only 8% of 360 farmers stated that their sows were transported under special conditions more than once per year.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…He argues that effectiveness of driver-initiated initiatives, to avoid additional suffering likely to be associated with transport of a compromised animal are questionable, and that there are different views about the types of conditions that constitute a compromised animal. In our recent survey among farmers delivering sows to the same slaughterhouse as in the present study ( Herskin et al, 2020 ), the reported use of the special condition transport was even lower than in the present one. Only 8% of 360 farmers stated that their sows were transported under special conditions more than once per year.…”
Section: Discussioncontrasting
confidence: 67%
“…Looking at the answers to several of the questions involved in the present survey (mentioned at least once as part of the answers to questions number 8, 14, 16, 18, and 20), it was clear that the drivers did consider hot weather a challenge to the welfare of the sows during transportation. In contrast to this, only 5% of the farmers chose “large influence,” when asked about the weather as a challenge for the sows, and 81% chose “no” or “slight” influence ( Herskin et al, 2020 ). The reasons for this difference are at present unclear, but may relate to the fact that drivers follow the sows on the journey and upon arrival, whereas farmers do not.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations